2020
DOI: 10.14814/phy2.14587
|View full text |Cite
|
Sign up to set email alerts
|

Decreased AMP‐activated protein kinase (AMPK) function and protective effect of metformin in neonatal rat pups exposed to hyperoxia lung injury

Abstract: We investigated the hypothesis that exposure of lungs at the saccular stage of development to hyperoxia leads to persistent growth arrest and dysfunction of 5’AMP‐activated protein kinase (AMPK), a key energy sensor in the cell. We exposed neonatal rat pups from postnatal day 1‐ day 10 (P1–P10) to ≥90% oxygen or control normoxia. Pups were euthanized at P4 or P10 or recovered in normoxia until euthanasia at P21. Half of the pups in each group received AMPK activator, metformin, or saline intraperitoneally from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…That similar pathologies were not observed with either AMPKα1 or AMPK-α2 deletion alone is also important, because this suggests redundancy of function that might afford new AMPK isoform-and thus pulmonary-selective therapeutic strategies against PPHN. Indeed, amelioration by metformin of PPHN [23][24][25] and pulmonary hypertension in the adult 5,27,91,92 has been noted 26 , which may be mediated, at least in part, through AMPK activation as opposed to reduced e ciency of redox and electron transfer at mitochondrial complex I per se 30 or inhibition of fructose-1,6 bisphosphatase 31 . Given that metformin is highly e cacious against type 2 diabetes, it is also interesting to note that AMPK de ciency 93 , PPHN [94][95][96] and pulmonary hypertension of the adult 97,98 are associated with obesity and type 2 diabetes (maternal with PPHN), not least because similar signs and symptoms are present even where no such comorbidity is evident [99][100][101] .…”
Section: Discussionmentioning
confidence: 99%
“…That similar pathologies were not observed with either AMPKα1 or AMPK-α2 deletion alone is also important, because this suggests redundancy of function that might afford new AMPK isoform-and thus pulmonary-selective therapeutic strategies against PPHN. Indeed, amelioration by metformin of PPHN [23][24][25] and pulmonary hypertension in the adult 5,27,91,92 has been noted 26 , which may be mediated, at least in part, through AMPK activation as opposed to reduced e ciency of redox and electron transfer at mitochondrial complex I per se 30 or inhibition of fructose-1,6 bisphosphatase 31 . Given that metformin is highly e cacious against type 2 diabetes, it is also interesting to note that AMPK de ciency 93 , PPHN [94][95][96] and pulmonary hypertension of the adult 97,98 are associated with obesity and type 2 diabetes (maternal with PPHN), not least because similar signs and symptoms are present even where no such comorbidity is evident [99][100][101] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, understanding how the lung vascular system homeostasis or health is maintained is pivotal to provide tailored therapies for BPD- PH in preterm infants. Emerging evidence indicates that AMPK promotes vascular health in several organs, including the lungs [ 21 , 46 , 47 , 48 , 49 , 50 ]. Furthermore, we recently observed that hyperoxia increases pulmonary AMPKα activation in a murine model of BPD-PH [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we recently observed that hyperoxia increases pulmonary AMPKα activation in a murine model of BPD-PH [ 19 ]. Yadav et al demonstrated that hyperoxia decreased pulmonary AMPK function in rat pups after 10days of hyperoxia, and the decreased p -AMPK levels persisted at P21, 10 days after pups were returned to normoxia [ 21 ]. Several other investigators have shown an increase in AMPK activation after shorter exposure to hyperoxia, in human lung fibroblasts and human umbilical vein endothelial cells (HUVECs) [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that neonatal rats exposed to hyperoxia after metformin treatment exhibited low mortality and reduced alveolar septum thickness and lung inflammation owing to the decreased influx of macrophages and neutrophils and improved vascularization (compared with the hyperoxia group) 20 . Recently, Yadav et al reported that metformin ameliorated hyperoxia‐induced lung injury and restored lung capillaries by enhancing AMPK function, in addition to increasing the expression of p‐AMPK and PGC‐1α 37 . Similarly, in our study, we found that metformin improved M2 type polarization of pulmonary macrophages, resulting in the upregulation of VEGF, which promoted vascular development in the hyperoxic lung.…”
Section: Discussionmentioning
confidence: 99%